Wind energy data for India - Mani, Anna, 1918-2001.; Mooley, D. A., 1922- (New Delhi : Allied, 1983)
Wind speed data for conversion of energy from atmospheric circulation in India.
Includes statistical tables.
Bibliography: p. 138-149.
Keywords: Wind power -- India